Pesan Dakwah dalam Buku “Menyembah Tuhan Yang Salah” - Imaduddin, Muhamad Khalid (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2022)
This paper thoroughly describes the forms of da'wah messages contained in the book Worshiping The Wrong God by Ahmad Rifa'i Rif'an in terms of the category of da'wah messages and message equalization techniques. The research method used in this research is a descriptive method, which is a series of procedures and also stages in carrying out research activities with the aim of solving problems with Ahmad Rifa'i Rif'an's book entitled "worshiping the Wrong God" which is the object, and documentation studies as methods used for data collection. Researchers collected these messages based on the categorization of dawah messages and messaging techniques. In terms of the category of da'wah messages, sharia da'wah message is the type of message that is most widely conveyed in the book. In terms of messaging techniques, informative messages are more delivered than persuasive and coercive messages. Keywords : Dawah Message, Message Category, Message Delivery